HPLC-MS/MS analysis of a traditional Chinese medical formulation of Bu-Yang-Huan-Wu-Tang and its pharmacokinetics after oral administration to rats. - Lee-Hsin Shaw; Lie-Chwen Lin; Tung-Hu Tsai (PLoS ONE, 2012)
Bu-yang-huan-wu-tang (BYHWT) is one of the most popular formulated traditional Chinese medicine prescriptions, and is widely for prevention of ischemic cardio-cerebral vascular diseases and stroke-induced disability. A specific high-performance liquid chromatography-tandem mass spectrometry (HPLC-MS/MS) has been developed and validated for simultaneous quantification of the nine main bioactive components, i.e., astragaloside I, astragaloside II, astragaloside IV, formononetin, ononin, calycosin, calycosin-7-O-β-d-glucoside, ligustilide and paeoniflorin in rat plasma after oral administration of BYHWT extract. This method was applied to investigate the pharmacokinetics in conscious and freely moving rats. No significant matrix effects were observed. The overall analytical procedure was rapid and reproducible, which makes it suitable for quantitative analysis of a large number of samples. Among them, three astragalosides and four isoflavones in A. membranaceus, ligustilide in Radix Angelicae Sinensis and Rhizoma Ligustici Chuanxiong and paeoniflorin in Radix Paeoniae Rubra were identified. This developed method was then successfully applied to pharmacokinetic studies of the nine bioactive constituents after oral administration of BYHWT extracts in rats. The pharmacokinetic data demonstrated that astragaloside I, astragaloside II, astragaloside IV and ligustilide presented the phenomenon of double peaks. The other herbal ingredients of formononetin, ononin, calycosin, calycosin-7-O-β-d-glucoside and paeoniflorin appeared together in a single and plateau absorption phase. These phenomenona suggest that these components may have multiple absorption sites, regulation of enterohepatic circulation or the gastric emptying rate, or there is ingredient-ingredient interaction. These pharmacokinetic results provide a constructive contribution to better understand the absorption mechanism of BYHWT and to support additional clinical evaluation.